1997
DOI: 10.1021/bi970593z
|View full text |Cite
|
Sign up to set email alerts
|

Distinct but Overlapping Epitopes for the Interaction of a CC-Chemokine with CCR1, CCR3, and CCR5

Abstract: Chemokines play an important role in inflammation. The mechanism via which they bind to more than one receptor and activate them is not well understood. The chemokines are thought to interact with their receptors via two distinct sites, one necessary for binding and the other for activation of signal transduction. In this study we have used alanine scanning mutagenesis to identify residues on RANTES that specifically interact with its receptors CCR1, CCR3, and CCR5 for binding and activation. Residues within a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
171
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(179 citation statements)
references
References 25 publications
(42 reference statements)
8
171
0
Order By: Relevance
“…5). The hydrophobic core includes F12, whose aromatic side chain has a pivotal role in CCR5 binding (6,(12)(13)(14)(15)(16)(17)(18). Indeed, our findings show a dramatic disruption in the ability to bind CCR5, when this residue is changed to alanine, validating the importance of the aromatic side chain for its binding activity.…”
Section: Insight Into Functional Interaction Of Mip-1␣ and The Ccr5supporting
confidence: 64%
See 1 more Smart Citation
“…5). The hydrophobic core includes F12, whose aromatic side chain has a pivotal role in CCR5 binding (6,(12)(13)(14)(15)(16)(17)(18). Indeed, our findings show a dramatic disruption in the ability to bind CCR5, when this residue is changed to alanine, validating the importance of the aromatic side chain for its binding activity.…”
Section: Insight Into Functional Interaction Of Mip-1␣ and The Ccr5supporting
confidence: 64%
“…The corresponding threonine residue in MIP-1␤ is important in dimer formation given its location at the hydrophobic dimer interface, where mutation to a charged residue will lead to a monomeric form (12). Interestingly, T8A mutation has no effect on the activity of RANTES with CCR1 (15). We propose that A9 could contribute to a hydrophobic core based around F12, which has been shown to have a role in CCR5 binding (Fig.…”
Section: Insight Into Functional Interaction Of Mip-1␣ and The Ccr5mentioning
confidence: 83%
“…Chemokines are divided into four families based on the pattern of cysteine residues (C, CC, CXC, and CX 3 C), and they exert their effects by binding and signaling through seven transmembrane G protein-coupled receptors (GPCRs) on the surface of leukocytes. Although the molecular details remain unclear, mutagenesis and NMR studies have revealed some of the structural requirements for receptor binding and activation (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). Collectively, these studies support a hypothesis whereby chemokines activate their receptor through a putative two-step mechanism.…”
Section: T He Directed Migration Of Leukocytes Into Areas Of Inflammamentioning
confidence: 78%
“…One important feature of the interaction involves epitopes scattered on the face of chemokine opposite the C-terminal helix, and contacts between this face and the N terminus of the receptor (6,7,11,(14)(15)(16)(17)(18). A second interaction is mediated by the disordered N-terminal region of chemokines preceding the first disulfide motif, which has been shown to be necessary for receptor activation (5,6,8,9,12,14,15,(19)(20)(21)(22).…”
Section: T He Directed Migration Of Leukocytes Into Areas Of Inflammamentioning
confidence: 99%
“…It is expressed inT lymphocytes, platelets, macrophages, tubular epithelium, synovial fibroblasts, endothelial cells and selected tumor cells [1,2]. CCL5 interacts with CCR1, CCR3, and CCR5 in various cell types [3].…”
Section: Introductionmentioning
confidence: 99%